The Evaluation of Prognostic Factors in Endoscopic Cartilage Tympanoplasty - Raza, Mohsin; Baig, Nasheed; Tahir, Muhammad; Bashir, Sheraz; Khan, Muhammad Zubair; Hussain, Sharbaz (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate prognostic factors affecting the success of endoscopic cartilage tympanoplasty, and to evaluate the results of endoscopic tympanoplasty in a tertiary care hospital. Study Design: Cross-sectional study. Place and Duration of Study: Department of ENT, Combined Military Hospital, Abbottabad Pakistan, from Aug 2022 to Aug 2023. Methodology: The study included 122 patients who underwent endoscopic transcanalicular tympanoplasty Type-I. We compared the effects of different variables on success rates and hearing improvement, including gender, affected side, location and size of the perforation, lack of tympanosclerosis, status of the external ear canal, state of the contralateral ear, and surgical background. Results: Variables that had a statistically significant impact on the surgical outcome (p <0.001) included myringosclerosis, contralateral ear status, affected side, gender, and perforation location. A significant correlation (p <0.001) was found between external ear canal wall protrusion, the size of perforation and interventional success. Conclusion: Endoscopic Type-I tympanoplasty has a good success rate in terms of both morphology and functionality. Myringosclerosis, contralateral ear status, affected side, gender, and perforation location significantly impact procedural success.